2022
DOI: 10.3390/antiox11040625
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia Treatment as a Promising Anti-Cancer Strategy: Therapeutic Targets, Perspective Mechanisms and Synergistic Combinations in Experimental Approaches

Abstract: Despite recent developments in diagnosis and treatment options, cancer remains one of the most critical threats to health. Several anti-cancer therapies have been identified, but further research is needed to provide more treatment options that are safe and effective for cancer. Hyperthermia (HT) is a promising treatment strategy for cancer because of its safety and cost-effectiveness. This review summarizes studies on the anti-cancer effects of HT and the detailed mechanisms. In addition, combination therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 202 publications
0
30
0
1
Order By: Relevance
“…13,94,96 Such effects are non-reversible and ultimately lead to cell death by necrosis. 97,98 The cellular and molecular mechanisms prompted by these photothermally induced events have been extensively reviewed elsewhere. 99–103…”
Section: Injectable Hydrogels For Cancer Pttmentioning
confidence: 99%
“…13,94,96 Such effects are non-reversible and ultimately lead to cell death by necrosis. 97,98 The cellular and molecular mechanisms prompted by these photothermally induced events have been extensively reviewed elsewhere. 99–103…”
Section: Injectable Hydrogels For Cancer Pttmentioning
confidence: 99%
“…For this experimental model of mild hyperthermia the temperatures 42°C and 43°C were selected [8]. Cancer cells were seeded in a 96-well plate at a density of 1.5 × 10 4 cells/well in 0.1 mL of media, followed by immersion in a temperature-controlled water bath (42°C or 43°C for mild hyperthermia and 37°C for normothermia) for 30 minutes.…”
Section: Hyperthermiamentioning
confidence: 99%
“…Hyperthermia is a potential option for the treatment of cancer since it has less side effects than conventional medications and is cost-effective in light of its substantial therapeutic benefit, particularly when paired with other treatments [6,7]. It has been reported that hyperthermia alone may not be adequate to eradicate cancerous cells but in combination with natural products, the limitations of hyperthermia may be overcome [8]. Thermic stimulation causes apoptosis but also activates transcription factors important in tumor survival, causing tumor cells to proliferate more rapidly and develop resistance to anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…High temperatures can induce receptor interacting protein kinase (RIPK)-1, fas-associated death domain (FADD). And the upregulated RIPK1 and FADD in tumor cells can associate with caspase-8 to induce apoptosis (53)(54)(55)(56). ROS promotes activation of death receptor pathways by inhibiting the production of Bcl-2/Bcl-xL and upregulating the expression of apoptotic-related proteins Bax.…”
Section: The Signaling Pathway Regulated By Phototherapy and Icbmentioning
confidence: 99%